Drowning in Neoliberalism: Rediscovering Constitutional Guarantees for Citizens - Zakirah Zakirah; Muhammad Gazali Rahman; Yos Sudarso; Thomi Rizqullah Habibi; Fakhry Amin (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Even though workers’ rights are generally important, this is often neglected, and changes towards neoliberalism occur. This can enrich a company and complicate the lives of workers. This research then aims to be able to see how to be able to reinvent the existence of guarantees for citizens when the country sinks into neoliberalism. The research method that will be used in this study uses a descriptive qualitative approach. The data used in this study come from different research results and previous studies, which still have relevance to the content of this research. The results of this study then found that neoliberalism eliminates the presence of guarantees for citizens to obtain their basic rights. The existence of a constitution can prevent public policy-making that erodes individual rights. Therefore, in general, the Indonesian state is not at all compatible with the concept of neoliberalism. This is because the elimination of the rights of citizens is very contrary to the contents of Pancasila itself.